Direct effect of bile salts and phospholipids on the physical properties of mucus. Issue 2 (February 1978) - Martin, G P; Marriott, C; Kellaway, I W
Abstract : Reflux of duodenal contents into the stomach has been implicated in the disruption of mucosal defence and the subsequent occurrence of gastric ulcer. The change produced in the rheological properties following the addition of bile salts and phospholipids to mucus samples was used to assess resultant structural changes. Sodium deoxycholate, sodium taurodeoxycholate, sodium glycocholate, and lysophosphatidylcholine decreased both viscosity and elasticity, indicating that structural breakdown had occurred, whereas phosphatidylcholine could not be shown to have any effect. It is therefore suggested that some of the ulcerogenic activity of naturally occurring surfactants may be associated with their ability directly to reduce mucus consistency.